An Interactive E-Learning Design for the grade 12 Tvl-Ict Programming Using Kotobee of Lagro Senior High School - Mamerto T. Goneda; Aileen L. Omadto; Kimberly M. Kho; John Terrence N. Casimiro; Aris Ruzzel C. Esguerra; Edison M. Gaudicos; Rein Jerry De la Cruz (International Journal on Integrated Education, 2021)
The research used an open-educational resource using Kotobee software to design interactive elearning for the Grade 12 TVL-ICT programming students of the Lagro Senior High School. The researchers wanted to assess the learners’ interest by using an interactive e-learning design made by the teachers. We used stratified and simple random sampling techniques to get the samples. The method and procedure of the research used are quantitative, descriptive, and developmental. The respondents of the study are selected Grade 12 TVL-ICT programming students. We used the Google form survey questionnaire to gather and collect the respondents’ data because of the online distance learning implemented amidst a pandemic situation for this Academic Year 2020-2021. The statistical treatment used in the study is mean, frequency, percentage, and Likert scale. As the results, 41 out of 50 respondents were answered and retrieved the survey data. There were 33 male and 8 female participants who answered the survey through Google form. The learner’s characteristics among the respondents were 76% are visual, 10% were auditory, and 7% were kinesthetic and pragmatist. Most of the learners have used gadgets for their online distance learning. 33 out of 41 respondents have used the mobile phone, and 26 responses used the tablets. When the teachers utilized e-learning through virtual online classes, the students’ challenges were the image blurred and very small to view, which had 26 responses out of 41 participants. Next, the text is too much, and the content is too hard to understand, which had 22 answers and agreed. Followed-by the text used is small, and the video presentation is pixelated. When the student’s losing interest talked about, the teacher has always presented a YouTube video clip related to the topic, which had the highest mean of 3.10 or agreed and placed in the rank 1. Second, using a simple PowerPoint presentation to discuss the lesson with no proper explanation had a mean of 3.05 o agree. Three (3) losing the interest of the student had the same mean of 2.80 or agreed. These are 1) hard to read the text from the teacher’s PowerPoint presentation, 2)the graphics are pixelated and inappropriate to the lesson, and 3) there is no interconnection of the image, colors, text, and shape used in the presentation. Meanwhile, the level of satisfaction to utilize the teacher’s interactive e-learning in terms of effectiveness shows that it is minimally satisfied or with an average mean of 2.31. The efficiency had an average of 2.46 or minimally satisfied.